Comparison of Stored Procedures on Relational Database Management System - Nahrun Hartono; Erfina Erfina (Tech-E, 2021)
Store procedure is a group of query stored in database catalogue which allows it to be recalled. Insert, update and delete data could performed using store procedure. Stored procedure is an alternative to optimize query performance and also to reduce security gap at interface level of a system. This research provides an overview implementation of stored procedure insert, update and deleting in two DBMS, MariaDB and PostgreSQL. Software developers prefer MariaDB and PostgreSQL because it is open-source, which means free. This research is an experimental research and descriptive analysis. This research data uses student data with amount of data 25000, 15000 and 5000 data. Research result show PostgreSQL require less processing time than MariaDB. Results of this research can used as a reference to design application programs which sometimes choose a DBMS is not a concern of developer.